Smelly primes – when olfactory primes do or do not work - Smeets, Monique A.; Dijksterhuis, Garmt B. (Frontiers in Psychology, 2014)
In applied olfactory cognition the effects that olfactory stimulation can have on (human) behavior are investigated. To enable an efficient application of olfactory stimuli a model of how they may lead to a change in behavior is proposed. To this end we use the concept of olfactory priming. Olfactory priming may prompt a special view on priming as the olfactory sense has some unique properties which make odors special types of primes. Examples of such properties are the ability of odors to influence our behavior outside of awareness, to lead to strong affective evaluations, to evoke specific memories, and to associate easily and quickly to other environmental stimuli. Opportunities and limitations for using odors as primes are related to these properties, and alternative explanations for reported findings are offered. Implications for olfactory semantic, construal, behavior and goal priming are given based on a brief overview of the priming literature from social psychology and from olfactory perception science. We end by formulating recommendations and ideas for a future research agenda and applications for olfactory priming.